Variación estacional de la composición proximal del mejillón Tagelus peruvianus (Bivalvia: Solecurtidae) del Golfo de Nicoya, Puntarenas, Costa Rica - Fonseca Rodríguez, Cristian (Universidad de Costa Rica, 2011)
Seasonal variation in proximate composition of mussels Tagelus peruvianus (Bivalvia: Solecurtidae) from the Gulf of Nicoya, Puntarenas, Costa Rica. Marine bivalves are a very important food source for human consumption, and species that has not been of traditional use as a fishery resource are gaining interest. Seasonal variation in proximate composition, condition index and energy or caloric content of the mussel Tagelus peruvianus were studied in the Gulf of Nicoya, Puntarenas, Costa Rica. From November 2007 to October 2008, a total of 35 to 40 specimens per month were collected. The proximate composition using the AOAC methods was determined. Results showed that the condition index during December, January and May decreased, indicative of two spawning periods and one gonadal resting phase. Soft tissues were respectively characterized by protein (61.9±4.3%), carbohydrates (15.7±2.4%), ash (14.0±1.9%) and lipids (8.5±1.7%). The average caloric content was 5.0±0.1kcal/g. The results showed that the decrease in protein and fat percentage, and calories content, occurred during the spawning seasons. We suggest that T. peruvianus has an optimal nutritional value for human consumption because of the low-fat and moderate protein content.